Prognostic impact of cytogenetic abnormalities in children and adolescents with mature B‐cell non‐Hodgkin lymphoma: A report from the Japanese Pediatric Leukemia/Lymphoma Study Group (JPLSG). Issue 7 (19th March 2015) - Sekimizu, Masahiro; Mori, Tetsuya; Kikuchi, Akira; Mitsui, Tetsuo; Sunami, Shosuke; Kobayashi, Ryoji; Fujita, Naoto; Inada, Hiroko; Takimoto, Tetsuya; Saito, Akiko Moriya; Watanabe, Tomoyuki; Fujimoto, Junichiro; et al.
<x xml:space="preserve">Abstract</x> Little information is available on cytogenetic abnormalities and their prognostic importance in childhood mature B‐cell non‐Hodgkin lymphoma (B‐NHL). We performed a review of 79 abnormal karyotypes in childhood B‐NHL treated by a uniform protocol. Del(17p) was independently associated with significantly inferior event‐free survival in Burkitt or Burkitt‐like lymphoma. The adverse prognosis of MYC/8q24 rearrangement, +7q or del(13q), was not observed, which had been suggested as risk factors in FAB/LMB96. Our results imply the possible existence of a biological difference among ethnicities and should be useful to narrow down the gene causing poor prognosis in childhood B‐NHL. Pediatr Blood Cancer 2015;62:1294–1296. © 2015 Wiley Periodicals, Inc.